Răspuns :
12x-3=9
12x=9+3
12x=12
x=1
b). 7x+11=4
7x=4-11
7x=-7
x=-1
c)3x+7=x-2
3x-x=-2-7
2x=-9
x=-4,5
d). 8x-3x-1=9
5x=9+1
5x=10
x=2
12x=9+3
12x=12
x=1
b). 7x+11=4
7x=4-11
7x=-7
x=-1
c)3x+7=x-2
3x-x=-2-7
2x=-9
x=-4,5
d). 8x-3x-1=9
5x=9+1
5x=10
x=2
a) 12x-3=9
12x=9+3
12x=12
x=12/12
x=1
b)7x+11=4
7x=4-11
7x=-7
x=-7/7
x=-1
c)3x+7=x-2
3x-x=-2-7
2x=-9
x=-9/2
x=-4,5
d)8x-(3x+1)=9
8x-3x-1=9
5x=10
x=10/5
x=2
12x=9+3
12x=12
x=12/12
x=1
b)7x+11=4
7x=4-11
7x=-7
x=-7/7
x=-1
c)3x+7=x-2
3x-x=-2-7
2x=-9
x=-9/2
x=-4,5
d)8x-(3x+1)=9
8x-3x-1=9
5x=10
x=10/5
x=2